Studi Literatur: Penerapan Model Pembelajaran Talking Stick untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Arini, Tri Rahayu; Salimi, Moh (Universitas Sebelas Maret, 2025)
The low learning motivation of elementary school students is a challenge in the world of education, so innovation is needed in participatory and fun learning models such as the talking stick learning model, which is the background of the research. This study aims to describe the influence of the talking stick learning model on learning motivation based on previous research findings. Literature studies are used as a research method obtained through scientific research articles from 2016-2025 found on Google Scholar as many as 30 relevant articles and used as a literature review then identified by reading, categorizing, analyzing, classifying, and describing. The results of the data analysis show that learning motivation increased significantly after the implementation of the talking stick model. This is proven by researchers who argue that the results of their research state that the talking stick model has an effect on increasing learning motivation. This means that the talking stick model is able to increase the level of learning motivation of elementary school students. It is recommended that teachers at the elementary school level can implement the talking stick model so that learning is more active and motivates students during the learning process.Motivasi belajar siswa sekolah dasar yang masih rendah menjadi tantangan dalam dunia pendidikan, sehingga diperlukan inovasi dalam model pembelajaran yang bersifat partisipatif dan menyenangkan seperti model pembelajaran talking stick yakni hal yang melatarbelakangi penelitian. Penelitian ini memiliki tujuan guna mendeskripsikan mengenai pengaruh model pembelajaran talking stick ke motivasi belajar yang didasarkan temuan penelitian terdahulu.Studi literatur dipakai sebagai metode penelitian yang didapatkan melalui artikel penelitian ilmiah mulai tahun 2016-2025 yang terdapat di Google Scholar sebanyak 30 artikel yang relevan dan dijadikan sebagai kajian pustaka kemudian diidentifikasi dengan membaca, mengkatagori, menganalisis, mengklasifikasikan, dan mendeskripsi. Hasil analisis data memperlihatkan motivasi belajar meningkat secara signifikan sesudah penerapan model talking stick. Hal tersebut dibuktikan oleh peneliti-peneliti yang berpendapat dari hasil penelitiannya menyebutkan model talking stick berpengaruh ke peningkatan motivasi belajar. Artinya model talking stick mampu menumbuhkan tingkat motivasi belajar siswa sekolah dasar. Disarankan untuk guru di tingkat sekolah dasar bisa melakukan penerapan model talking stick agar pembelajaran semakin aktif serta memotivasi siswa saat proses belajar.